2014
DOI: 10.1002/car.2305
|View full text |Cite
|
Sign up to set email alerts
|

Health, Developmental and Support Needs of Vulnerable Children – Comparing Children in Foster Care and Children in Need

Abstract: Health, Developmental and Support Needs of Vulnerable ChildrenComparing Children in Foster Care and Children in NeedThe health needs of children in foster care (FC) have been well described and pathways to health assessment established. Such pathways for other vulnerable children are scarce. We aimed to describe the health and service needs of children attending community paediatric (CP) clinics specifically set up for children exposed to psychosocial risk factors in South Western Sydney (SWS), and to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A complete list is beyond the scope of this article, so we refer the reader to the above articles and these additional manuscripts (Arora et al 2014 ; Becker and Barth 2000 ; Lauver 2008 ; Ogg et al 2015 ; Rubin et al 2004 ). While many articles report children in foster care have higher rates of medical health problems (e.g., Ringeisen et al 2008 ), a study by Raman and Sahu ( 2014 ) did not find any differences between children in foster care and children at risk living in with their parents. The identified risk factors for developing medical problems are being male, being older, having a longer stay in foster care and having had multiple placements (Ringeisen et al 2008 ; Rubin et al 2004 ; Sullivan and van Zyl 2008 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A complete list is beyond the scope of this article, so we refer the reader to the above articles and these additional manuscripts (Arora et al 2014 ; Becker and Barth 2000 ; Lauver 2008 ; Ogg et al 2015 ; Rubin et al 2004 ). While many articles report children in foster care have higher rates of medical health problems (e.g., Ringeisen et al 2008 ), a study by Raman and Sahu ( 2014 ) did not find any differences between children in foster care and children at risk living in with their parents. The identified risk factors for developing medical problems are being male, being older, having a longer stay in foster care and having had multiple placements (Ringeisen et al 2008 ; Rubin et al 2004 ; Sullivan and van Zyl 2008 ).…”
Section: Resultsmentioning
confidence: 90%
“…Based on over 30.000 case files, about 6% of children in foster care have so-called complex needs, which means having co-occurring physical health problems, emotional problems and the need for specialized services (Yampolskaya et al 2014 ). The most common health problems mentioned in the literature are incomplete immunization (Hill and Watkins 2003 ; Kaltner and Rissel 2011 ; Kling et al 2016 ; Nathanson and Tzioumi 2007 ; Raman and Sahu 2014 ; Rodrigues 2004 ), vision problems (Chernoff et al 1994 ; Nathanson and Tzioumi 2007 ; Steele and Buchi 2008 ; Takayama et al 1998 ), and respiratory problems (Nathanson and Tzioumi 2007 ; Ringeisen et al 2008 ; Rodrigues 2004 ; Takayama et al 1998 ). Other medical conditions that are also often encountered in the foster care population are obesity, dental problems, skin conditions, STD’s, infections and allergies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies are presented in Appendix Table 1, (available online). The studies primarily came from the United Kingdom (n=15), 18,20,24,26,28,[30][31][32][33]36,38,39,41,43,46 the U.S. (n=9), 19,22,23,29,37,40,42,48,49 and Australia (n=6), 17,27,35,44,45,47 with a smaller number from Italy (n=1), 21 and Sweden (n=2). 25,34 They included 29 peer-reviewed journal publications, three government reports, and one thesis.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Studies from other countries similarly show high rates of health needs among youth in placement. In an Australia‐based study comparing health needs of vulnerable children with those of children in foster care, Raman and Sahu () found that only vision concerns were statistically more common among youth in foster care (at 34%) compared with youth in parental care (14%). Surprisingly, none of the other health areas, including dental problems, showed any significant differences.…”
Section: Introductionmentioning
confidence: 99%